2016
DOI: 10.1002/cne.24095
|View full text |Cite
|
Sign up to set email alerts
|

Descending projections from the inferior colliculus to the dorsal cochlear nucleus are excitatory

Abstract: Ascending projections of the dorsal cochlear nucleus (DCN) target primarily the contralateral inferior colliculus (IC). In turn, the IC sends bilateral descending projections back to the DCN. We sought to determine the nature of these descending axons in order to infer circuit mechanisms of signal processing at one of the earliest stages of the central auditory pathway. An anterograde tracer was injected in the IC of CBA/Ca mice to reveal terminal characteristics of the descending axons. Retrograde tracer depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 106 publications
(152 reference statements)
2
20
0
Order By: Relevance
“…Aberrant activity in any cochlear nucleus subregions can trigger upstream changes as cochlear nucleus neurons relay auditory signals to higher areas of the auditory pathway (Kraus et al, 2011;Coomber et al, 2015). Abnormal activity from auditory cortex and inferior colliculus can also produce downstream alterations in the DCN as its cells receive feedback through descending auditory fibers (Winer and Prieto, 2001;Milinkeviciute et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activity in any cochlear nucleus subregions can trigger upstream changes as cochlear nucleus neurons relay auditory signals to higher areas of the auditory pathway (Kraus et al, 2011;Coomber et al, 2015). Abnormal activity from auditory cortex and inferior colliculus can also produce downstream alterations in the DCN as its cells receive feedback through descending auditory fibers (Winer and Prieto, 2001;Milinkeviciute et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Anterograde trans-synaptic labeling of DCN neurons that receive input from IC To test the hypothesis that fibers from IC drive cells in the granule cell domain, the identity of those cells must be determined. We focused on the ipsilateral IC-DCN projection because it is much larger than the contralateral projection (Milinkeviciute et al, 2017). We injected a Cre-recombinase (Cre) expressing adeno-associated virus (AAV1-Syn-Cre) into the right IC of Ai9 reporter mice that express the red fluorescent protein tdTomato in cells that contain Cre (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AAV1-Chronos-GFP (1.4e13 GC/ml, Addgene) was used instead of the ChR2-Venus virus in a single experiment that yielded ChR2evoked EPSCs in one granule cell and one Golgi cell. We did not differentiate whether the injection site included the central nucleus or the lateral/external cortex of the IC, because previous work in the mouse showed that all major subdivision of the IC project to DCN (Milinkeviciute et al, 2017).…”
Section: Viral Injectionsmentioning
confidence: 99%
See 2 more Smart Citations